A62 POST COLONOSCOPY COLORECTAL CANCERS IN ALBERTA. A PROCESS FOR IDENTIFYING TRUE CASES. (1st March 2018) - Mohamed, M S; Johnson, D; Sadowski, D; Wong, C
Abstract: Background: Determining Post Colonoscopy Colorectal Cancer (PCCRC) rates is one of the most important measures of colonoscopy quality. Most commonly, PCCRCs are the result of technical factors surrounding the colonoscopy such as inadequate bowel preparation, incomplete examination, missed early lesions and failure to adhere to follow-up guidelines. As these factors are amenable to quality interventions, we set out to identify PCCRC cases from a population perspective with a view to calculating incidence rates. Aims: Our objective was to develop a framework for data gathering and analysis in order to identify PCCRC cases and rates in Alberta in order to obtain a clearer understanding of the underlying causes of PCCRC where potential quality interventions might be applied. Methods: This was a retrospective population based review of all cases of colorectal cancer (CRC) diagnosed in Alberta in 2013. Data from the Alberta Cancer Registry (ACR) was linked to the Discharge Abstract Database (DAD), the National Ambulatory Care Reporting System (NACRS) and Alberta Ambulatory Care Reporting System (AACRS) databases to determine the timing of antecedent colonoscopies. We defined a PCCRC as a case identified in the ACR with ICD-10 codes for colorectal cancer with an antecedent colonoscopy greater than 6 months but less than 3 years prior to the diagnosis of CRC. Individual chart reviews were carried out to exclude high-risk groups such as IBD or genetic syndromes and to determine lesion location. Results: Before a PCCRC rate could be calculated, we identified that the initial data linking process provided a number of cases that required further in depth review to determine if they met inclusion and exclusion criteria. Subsequently, through an iterative process of chart review, we developed a decision analysis framework (see Figure1), that provided a rational basis for case exclusion as well as systematic categorization of PCCRC root causes. Our analysis also identified areas for future quality improvement initiatives: such as the failure to arrange follow-up after poor bowel preparation or advanced lesions. We also identified cases where access to timely care resulted in the development of a PCCRC. Conclusions: Attempts to identify cases of PCCRC through database linkage identifies cases that require in depth analysis to determine eligibility. We have developed an algorithm that provides a rational basis for case exclusion as well as systematic categorization of PCCRC root causes. Funding Agencies: None